2021
DOI: 10.1093/pastj/gtab024
|View full text |Cite
|
Sign up to set email alerts
|

Viewpoint New Approaches to the ‘Plague of Justinian’

Abstract: This viewpoint is meant as a contribution to debate over the nature and significance of the ‘Justinianic Plague’, which struck Western Eurasia between the sixth and eighth centuries Ce, and the methodological challenges posed by attempting to reconcile historical evidence with that derived from the realm of the Natural Sciences. In recent years, major advances have been made in our genetic understanding of the Justinianic Plague. Yet growing scientific interest in the disease has coincided with a concerted eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…Indications of a societal crisis and a population drop in northern Europe during the Nordic Late Iron Age have long been debated (e.g. Näsman & Lund, 1988), with causes such as the fall of the West Roman Empire, the Justinian Plague (Harbeck et al, 2013; Sarris, 2022), and, particularly, climate change due to volcanic eruptions in the sixth century ad (Sigl et al, 2015; Büntgen et al, 2016) being cited. Several studies have shown that a dust veil from large-scale volcanic eruptions during the sixth century ad , particularly in ad 536, 540, and 547, resulted in the cooling of the Northern Hemisphere on a global scale (Larsen et al, 2008; Sigl et al, 2015; Büntgen et al, 2016; Toohey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indications of a societal crisis and a population drop in northern Europe during the Nordic Late Iron Age have long been debated (e.g. Näsman & Lund, 1988), with causes such as the fall of the West Roman Empire, the Justinian Plague (Harbeck et al, 2013; Sarris, 2022), and, particularly, climate change due to volcanic eruptions in the sixth century ad (Sigl et al, 2015; Büntgen et al, 2016) being cited. Several studies have shown that a dust veil from large-scale volcanic eruptions during the sixth century ad , particularly in ad 536, 540, and 547, resulted in the cooling of the Northern Hemisphere on a global scale (Larsen et al, 2008; Sigl et al, 2015; Büntgen et al, 2016; Toohey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is not the first coronavirus, only the most documented one (Liu, Kuo & Shih, 2020). The acclaimed foremost major pandemic named 'Justinianic Plague' and scientifically dated to have raged from circa 541 CE to 750 CE also claimed as many as 30 to 60 million lives (Mordechai, Eisenberg, Newfield, Izdebski, Kay, J. E., & Poinar, 2019;Sarris, 2022;Meier, 2020). Like the Black Death and the current COVID-19, the plague spread slowly and quickly across the globe, including Africa, the Americas, and the Middle East (Green, 2018;Chouin, 2018;Glatter & Finkelman, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nas palavras de Monica Green, o superpoder da Genética é que ela "nos permite escrever a história da doença a partir da perspectiva do patógeno, não simplesmente da perspectiva necessariamente cega da observação humana (macroscópica)" (GREEN, 2021). É verdade que nós não podemos ainda contar com nada semelhante ao sequenciamento genético da bactéria Yersinia pestis e à descoberta de esqueletos infectados por esse agente causador da peste bubônica, os quais têm revolucionado os estudos sobre a Peste de Justiniano e a Peste Negra (GREEN, 2020;SARRIS, 2022). Não temos, por exemplo, nenhuma evidência, na forma de DNA, de patógeno antigo recuperado do esqueleto de uma vítima da Peste Antonina (HARPER, 2021, p. 194-195).…”
Section: Introductionunclassified